Obesity Paradox: Laboratory Findings in Uncomplicated Obesity. Is Bias a Plausible Explanation?. (24th November 2020) - Nwogbo, Okechukwu V; Ullah, Asad; Singh, Gurmukh
Abstract: Objectives: Obesity predisposes to multiple diseases, such as heart disease, diabetes, stroke, arthritis, and malignancy. However, obese patients have better outcomes than normal-weight patients with some of these disorders, including those admitted to critical care units. We compared the results for common laboratory tests in patients with uncomplicated obesity against the findings in normal-weight patients. Methods: Patients who had a comprehensive metabolic profile test were identified. Patients with acute and/or chronic debilitating disorders were excluded, and the laboratory parameters were compared among 4 groups based on body mass index. Results: With the exception of elevated triglycerides and lower high-density lipoprotein in obese and morbidly obese patients, laboratory findings were not meaningfully different from those in normal-weight patients. Conclusions: The obesity paradox of better outcomes in obese patients admitted to critical care units could not be explained on the basis of lower additional disease burden necessitating critical care admission due to abnormal laboratory values at the baseline. It is conceivable that unconscious bias against obese patients, with lower disease burden than normal-weight patients, triggers their admission to critical care, thus creating the appearance of better outcomes.